Analysis of Risks and Barriers associated with Mobile Money Transactions in The Western Region of Ghana. A Case Study of Sekondi-Takoradi Metropolis - Yawson, Charles (Technium Social Sciences Journal, 2022)
This study was commissioned to investigate the level of risk and Barriers associated with mobile money transactions in Ghana. It seeked to assess the level of risk perception among mobile money users and merchants. In addition to the above, the paper examined behaviour and attitudes exhibited by customers and merchants during mobile money transactions. This was to help in ascertaining whether or not both parties are being susceptible to high risk or not. The empirical evidence showed that, mobile money transactions have become the most popular and preferred method of sending and receiving payments in Africa since the vast majority of the Continent’s population are rural dwellers with Ghana not being an exception. The population for the study was customers and merchants of the MTN brand of mobile money from which five hundred and fifty (550) respondents were sampled for the study. The methodology used was quantitative where primary data was sort through administration of questionnaire within the Sekondi-Takoradi Metropolis. The paper discovered a higher-level patronage of mobile money among respondents. It emerged that, there were eminent risks associated with mobile money operations although the growth prospects appeared to be greater.